2017
DOI: 10.1111/cns.12703
|View full text |Cite
|
Sign up to set email alerts
|

Roles of autophagy and endoplasmic reticulum stress in intracerebral hemorrhage‐induced secondary brain injury in rats

Abstract: At 6 hours after ICH, excessive autophagy may participate in ER stress-induced brain injury; at 7 days after ICH, autophagy could enhance the protection of ER stress inhibitor possibly via clearing up the cell rubbish generated due to the early-stage damaged autophagic flux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 49 publications
(86 reference statements)
2
48
0
Order By: Relevance
“…As autophagy plays a critical role in the secondary injury mechanism of SCI, we examined whether the beneficial action of EPO on SCI was mediated by autophagy in our model system. Knowing that the conversion from LC3‐I to LC3‐II and expression of Beclin 1 are indispensable for the formation and expansion of autophagosomes, we detected these autophagic markers at 1, 3, and 7 days after injury to examine the temporal pattern of autophagic activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As autophagy plays a critical role in the secondary injury mechanism of SCI, we examined whether the beneficial action of EPO on SCI was mediated by autophagy in our model system. Knowing that the conversion from LC3‐I to LC3‐II and expression of Beclin 1 are indispensable for the formation and expansion of autophagosomes, we detected these autophagic markers at 1, 3, and 7 days after injury to examine the temporal pattern of autophagic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, autophagy has been demonstrated to be an important therapeutic mechanism for injuries of CNS such as SCI and several CNS degeneration diseases such as Alzheimer's disease. Accumulating evidence has shown that autophagy is induced after SCI, and the impairment of autophagy has been addressed to aggravate the secondary injury. The AMP‐activated protein kinase (AMPK) acts as an energy sensor responding to stress conditions such as oxidative stress and deprivation of nutrition, which also acts as a key player in autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…As a lysosomal degradative pathway, autophagy is essential for survival and maintaining cellular homeostasis. In addition, autophagy is involved in diverse diseases and injuries (Jiang et al, 2015), including the pathological processes during ICH (Duan et al, 2017;Li et al, 2018c). Moreover, recent studies have demonstrated that oxidative stress contributes to autophagy (Duan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that autophagy pathway activation was detected in neurons after ICH [6]. Increasing evidence has indicated that the role of autophagy in ICH pathology is crucial [23]. MST4 plays multiple roles Representative western blot bands for MST4, pAKT, AKT, and LC3 expression in sham and ICH mice 12 h following ICH.…”
Section: Discussionmentioning
confidence: 98%